Report on Inception Workshop: Strengthening national capacities and policies for food systems analysis and transformation in Ghana - Asante, Felix A.; Asante, Seth (International Food Policy Research Institute, 2024)
This report is produced from the proceedings of the Inception workshop on “Strengthening National Capacities and Policies for Food Systems analysis and Transformation in Ghana” project held on Wednesday, 2nd August 2023 at Alisa Hotel, Accra. The workshop aimed to provide a comprehensive overview of the project and outlined its objectives, and timeline, alongside a review of the current landscape of the Ghana’s Food Systems Transformation. It brought together various stakeholders and institutions in the Ghanaian food systems. The workshop facilitated valuable discussions among participants to gather insights and inputs for the project's advancement (see attached list of participants). Three distinct presentations – project overview, project deliverables and timelines, and food systems diagnostics and tools as well as trade-offs and opportunities – were made at the workshop.